Anxiety and Stigma in Dementia: A Threat to Aging in Place - Riley, Rebecca J. (2014)
The number of Americans with dementia is expected to increase as the population ages. Developing dementia is feared by many older adults and may result in anxiety in persons with dementia (PwD). This article focuses on anxiety, one of the least understood symptoms associated with dementia in community-dwelling older adults, the stigma of dementia, and the relationship between anxiety and stigma in dementia. When undetected and untreated, anxiety and associated stigma can adversely affect quality of life and the ability to age in place. The paper begins by describing dementia-related anxiety. Next, based on research by the authors and others, the association between stigma and anxiety is examined. The paper concludes with recommendations for assessment and treatment of anxiety and stigma in persons with dementia that will better allow them to age in place.